Structure of the Seagrass Community, In Poopoh Beach Waters, Tombariri District, Minahasa Regency, North Sulawesi Province - Mamonto, Riswanto; Kondoy, Khiristin Ivone Fisye; Wantasen, Adnan S.; Kepel, Rene Charles; Pratasik, Silvester Beny; Menajang, Febry Susana Ivone (Sam Ratulangi University, 2024)
Seagrass are flowering plants (Angiosperms) that are fully adapted to life immersed in the sea. This plant consists of rhizomes, leaves and roots, (Rhizomes are stems that sink and creep horizontally, leave and flower, and grow roots). It is these rhizomes and roots that hold back the waves and currents on seagrass plants. The purpose of this study was to determine seagrass species, species density, relative density, species frequency, relative frequency, species closure, relative closure, important value index, diversity index, domination index and aquatic environmental conditions. There are 4 species of seagrass found in the waters of Poopoh Beach, namely, Thalassia hemprichii, Enhalus acoroides, Halodule pinifolia, Halophila ovalis. The number of stands of seagrass species in the study area ranged from 53-965 individuals, species density (17.67-321.67) individuals/m2, relative density (3.98-72.61%), frequency (0.045-0.90), relative frequency (3.57-71.42%), species closure (0.41-7.31), relative coverage (1.04-78.12%), seagrass importance value index in Poopoh Beach waters shows that Thalassia hemprchii has the highest importance value index among the other 3 seagrass species namely (212.85%), diversity index (0.97), species dominance index (0.11-0.44%/m²). Environmental conditions in the waters of Poopoh Beach, which has a temperature range of 38°C, a salinity of 35‰, has a substrate of sand, sand mixed with mud, muddy and coral fragments. Keywords: Poopoh Beach, Seagrass, Community Structure. Abstrak Lamun adalah tumbuhan berbunga (Angiospermae) yang sepenuhnya menyesuaikan diri dengan hidup terbenam dalam laut. Tumbuhan ini terdiri dari rhizoma, daun dan akar, (Rhizoma adalah batang yang terbenam dan merayap secara mendatar, berdaun dan berbunga, serta tumbuh akar). Rhizoma dan akar inilah yang menahan hempasan ombak dan arus pada tumbuhan lamun. Tujuan penelitian ini adalah untuk mengetahui jenis-jenis lamun, kerapatan spesies, kerapatan relatif, frekuensi jenis, frekuensi relatif, penutupan jenis, penutupan relatif, indeks nilai penting, indeks keanekaragaman, indeks dominasi dan kondisi lingkungan perairan. Spesies lamun yang ditemukan diperairan Pantai Poopoh berjumlah 4 spesies yaitu, Thalassia hemprichii, Enhalus acoroides, Halodule pinifolia, Halophila ovalis. Jumlah tegakan spesies lamun dilokasi penelitian berkisar dari 53-965 individu, kerapatan spesies (17,67-321,67) individu/m2, kerapatan relatif (3,98-72,61%), frekuensi (0,045-0,90), frekuensi relatif (3,57-71,42%), penutupan jenis (0,41-7,31), penutupan relatif (1,04-78,12%), indeks nilai penting lamun diperairan Pantai Poopoh menunjukkan bahwa Thalassia hemprchii memiliki indeks nilai penting paling tinggi diantara ke 3 spesies lamun lainnya yakni (212,85%), indeks keanekaragaman (0,97), indeks dominasi spesies (0,11-0,44%/m²). Kondisi Lingkungan diperairan Pantai Poopoh yakni mamiliki kisaran suhu 28°C, salinitas 30‰, memiliki substrat pasir, pasir campur lumpur, berlumpur dan patahan karang. Kata Kunci: Pantai Poopoh, Lamun, Struktur Komunitas.